1985
DOI: 10.1128/mcb.5.7.1772
|View full text |Cite
|
Sign up to set email alerts
|

A mutation at the ATP-binding site of pp60v-src abolishes kinase activity, transformation, and tumorigenicity.

Abstract: We constructed a mutant, called RSV-SF2, at the ATP-binding site of pp6Ov-rc. In this mutant, lysine-295 is replaced with methionine. SF2 pp6ov-src was found to have a half-life similar to that of wild-type pp6Ov-c and was localized in the membranous fraction of the cell. Rat cells expressing SF2 pp6Ov-src were morphologically untransformed and do not form tumors. The SF2 pp6Ov-S isolated from these cells lacked kinase activity with either specific immunoglobulin or other substrates, and expression of SF2 pp6O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(53 citation statements)
references
References 49 publications
4
49
0
Order By: Relevance
“…We used three Src mutants: (1) Y527F c-Src (constitutively-active) (Cartwright et al, 1987); (2) K297M Src (kinase-inactive) (Snyder et al, 1985); and (3) dl155 Src (contains a three amino acid deletion in the phosphotyrosine binding pocket of the SH2 domain) (Moyers et al, 1993). Previously, we showed that the dl155 Src mutant has reduced binding to RACK1 (Chang et al, 2001).…”
Section: Rack1 Is An Endogenous Substrate For Srcmentioning
confidence: 99%
See 1 more Smart Citation
“…We used three Src mutants: (1) Y527F c-Src (constitutively-active) (Cartwright et al, 1987); (2) K297M Src (kinase-inactive) (Snyder et al, 1985); and (3) dl155 Src (contains a three amino acid deletion in the phosphotyrosine binding pocket of the SH2 domain) (Moyers et al, 1993). Previously, we showed that the dl155 Src mutant has reduced binding to RACK1 (Chang et al, 2001).…”
Section: Rack1 Is An Endogenous Substrate For Srcmentioning
confidence: 99%
“…pGEM K297M src was a gift from Tony Hunter (The Salk Institute for Biological Studies, La Jolla, CA, USA; Snyder et al, 1985). Src inserts from these plasmids or Y527F c-src (Cartwright et al, 1987) were subcloned into pcDNA3 (Introgen, La Jolla, CA, USA) to create pcDNA3 c-src, dl155 c-src, K297M c-src and Y527F c-src, and transiently expressed in CHO cells (Chang et al, 1998(Chang et al, , 2001).…”
Section: Plasmidsmentioning
confidence: 99%
“…DN-SHPT1D, a mutant phosphotyrosine phosphatase type 1D which incorporates a carboxy terminal deletion of 60 amino acids required for its tyrosine phosphorylation, was from Dr. Ben Neel (Beth Israel Hospital) [40]. Wild-type Src, dominant negative Src (K298MSrc) [41] and constitutively activated Src (Src Y527F) which lacks a key inhibitory phosphorylation site [42] were from Dr. L. Luttrell (Duke University).…”
Section: Dna Constructsmentioning
confidence: 99%
“…Genistein, a broad-spectrum tyrosine kinase inhibitor, markedly attenuated the ability of 5-HT to activate ERK and NHE, whereas the structurally similar but inactive compound, daidzein, had no effect, supporting the involvement of tyrosine kinase(s) in both pathways (Table 1). PTP1D is a cytosolic phosphotyrosine phosphatase which has been shown to be a critical positive regulator of tyrosine kinase signals (DNA synthesis and ERK activation) initiated by both growth factor and G proteincoupled receptors [38][39][40][41][42][43][44][45][46][47][48][49]. Transfection of a cDNA construct encoding a mutant inactive PTP1D (∆PTP1D) molecule effectively blocked 5-HT-stimulated ERK, but had no effect on NHE activity.…”
Section: Figure 2 Lack Of Involvement Of Pkc In 5-ht-mediated Increasmentioning
confidence: 99%
“…1). NYmet295 (10) and 5Hmet295 (21), derivatives of RSV and NY5H, respectively, are tyrosine kinase-defective mutants with point mutations in the ATP binding site (38). NYT10-1 is a substitution of Arg-Ser-Asp for residues 412 to 416 of p60vsrc (6).…”
Section: Methodsmentioning
confidence: 99%